Adapting the graduation efficiency index to provide a consistent basis for assessment of student progress towards graduation. (2nd October 2018) - Killingsworth, Brenda L.; Mansaray, Mahmud A.; Rhodes, Len
ABSTRACT: Graduation efficiency is of top concern for institutions of higher education throughout the world. Increasingly, accountability metrics have come under scrutiny as policymakers seek to ensure public resources are efficiently used. Traditionally, higher education policymakers in the USA and Europe have used graduation rate as an accountability measure to assess a university's efficient use of resources. This time-to-degree method, however, does not take into account the shift in student demographics from a traditional full-time student to the diverse group of students pursuing higher education through varied paths, including balancing work with reduced course loads, studying abroad, completing internships, among others. These changes suggest additional accountability measures are needed to accurately capture student progress as it relates to resource utilisation. This research adapts the Graduation Efficiency Index proposed by Gillmore and Hoffman (1997) to a cohort-based model to allow for evaluating retention policies implemented by cohorts to improve student progress.